2002
DOI: 10.1016/s0014-5793(02)02580-2
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced activation of bound plasminogen on Staphylococcus aureus by staphylokinase

Abstract: Activation of plasminogen (plg) to plasmin by the staphylococcal activator, staphylokinase (SAK), is effectively regulated by the circulating inhibitor,Here it is demonstrated that intact Staphylococcus aureus cells and solubilized staphylococcal cell wall proteins not only protected SAK-promoted plg activation against the inhibitory effect of K K 2 AP but also enhanced the activation. The findings suggest that the surface-associated plg activation by SAK may have an important physiological function in helping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 31 publications
2
63
0
Order By: Relevance
“…Enolase has also been identified as a novel plasminogen receptor on the surface of many eukaryotic cells (Miles et al, 1991; Nakajima et al, 1994). This unexpected feature has also been described in several bacteria (such as Staphylococcus aureus and many streptococci), fungi and nematodes (Bergmann et al, 2001;Jolodar et al, 2003;Jong et al, 2003;Molkanen et al, 2002;Pancholi & Fischetti, 1998;Sharma et al, 2006). While the role of plasminogen as an important component in streptoccoci adhesion is well established (Pancholi et al, 2003), the role of enolase in bacterial adherence and host cell invasion has not, to our knowledge, been investigated previously.…”
Section: Introductionmentioning
confidence: 69%
“…Enolase has also been identified as a novel plasminogen receptor on the surface of many eukaryotic cells (Miles et al, 1991; Nakajima et al, 1994). This unexpected feature has also been described in several bacteria (such as Staphylococcus aureus and many streptococci), fungi and nematodes (Bergmann et al, 2001;Jolodar et al, 2003;Jong et al, 2003;Molkanen et al, 2002;Pancholi & Fischetti, 1998;Sharma et al, 2006). While the role of plasminogen as an important component in streptoccoci adhesion is well established (Pancholi et al, 2003), the role of enolase in bacterial adherence and host cell invasion has not, to our knowledge, been investigated previously.…”
Section: Introductionmentioning
confidence: 69%
“…EbpS is implicated in interactions between S. aureus and elastin, one of the major protein components of the extracellular matrix (31,32). Finally, Sak, the staphylokinase, may have an important physiological function in helping cells to disseminate in host tissue by activating plasminogen (28). A comparison of candidates for YycG/YycF regulation in B. subtilis and S. aureus reveals several similarities.…”
Section: See Materials and Methods) His-tagged Yycf Andmentioning
confidence: 99%
“…It has also been shown that activation of plasminogen to plasmin by staphylokinase is not only protected from the inhibitor, ␣ 2 -antiplasmin, but the activation is enhanced in the presence of S. aureus cells and solubilized staphylococcal cell walls (45). It was shown that these putative plasminogen-binding proteins were IMP dehydrogenase, ␣-enolase, and ribonucleotide reductase subunit 2 (45).…”
Section: Vol 190 2008 Extracellular Protein Profile Of S Aureus Uamentioning
confidence: 99%
“…It was shown that these putative plasminogen-binding proteins were IMP dehydrogenase, ␣-enolase, and ribonucleotide reductase subunit 2 (45). ␣-Enolase has also been shown to bind laminin on the surface of S. aureus (7).…”
Section: Vol 190 2008 Extracellular Protein Profile Of S Aureus Uamentioning
confidence: 99%